Fenomena Internet Trolling, sebuah Bentuk Kejahatan Siber - Nadia Ilona Bilondatu; Vinita Susanti (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article offers a discussion of a form of cybercrime, namely internet trolling, which, although, isn’t as frequently discoursed as the other online deviant behaviors, but it has started to become quite a phenomenon of its own lately, and has the potential to disrupt and damage public order and social order prevailing in the society. This article aims to provide an explanation and offer a brief analysis of the behavior of internet trolling; how it differs from several other online antisocial behaviors (ASOB); analysis of psychological and social causal factors and briefly discusses the characteristics of the perpetrators, criminological aspects and legal aspects related to the behavior, referring to the articles in the Criminal Code (KUHP) and the Law on Information and Electronic Transactions (ITE Law); also, points on how to handle this issue, in terms of what should be done if you become a victim of internet trolling and prevention steps as closing. This article was prepared by conducting research on document analysis in various forms, including laws and regulations, survey results and previous research, journal articles and various articles from the mass media